Answer:
The sign of the product will be positive.
Explanation:
You are going to end with a positive result because there are two positive numbers and two negative numbers.
When you multiply two negatives, -3 and -2, you get a positive.
When you multiply two positives, 3 and 4, you get a positive.
Multiply the positive result from the two negatives with the positive result from the two positive and you get another positive.
More proof:
(3)(-3)(-2)(4) = (3)(4)(-3)(-2)
3 * 4 = 12
- 3 * (- 2) = 6
12 * 6 = 72